Building Entrepreneurship Environment For Students Through Balinese Speaking Skills - Suardiana, I Wayan (Udayana Journal of Social Sciences and Humanities; Vol 2 No 2 (2018): UJoSSH, September 2018, 2018)
Efforts to innovate in language care is done by developing a model of skills that can be used as a provision of life by the speaker. Balinese language skills that will be offered in oral level such as mapidarta art (speech / orator), become ugrawakya /MC (Master of Ceremony), madarmawacana art (sermon), art of masatua (telling) Bali, as broadcaster (radio and TV); in the level of writing covers the art of writing opinion, writing reportoar in relation as a journalist. In this study only disclosed about the guide (model) of art into ugrawakya /MC (Master of Ceremony). This research data is a qualitative data that is extracted from the relevant books to guide or direct someone to be able to become a ugrawakya (MC) well. Methods of data collection is done by library study assisted by the technique of record. Data were analyzed by analytic descriptive method with deductive-inductive technique, and presented by informal method.